Correlation between cord blood bilirubin level and incidence of hyperbilirubinemia in term newborns - Rudy Satrya; Sjarif Hidayat Effendi; Dida Akhmad Gumida (Indonesian Pediatric Society, 2009)
Background Discharging healthy term newborns from thehospital after delivery at increasingly earlier postnatal ages hasrecently become a common practice due to medical, social, andeconomic reasons, however it contributes to readmission becauseof jaundice.Objective To investigate the correlation between level of cordblood bilirubin and development of hyperbilirubinemia amonghealthy term newborns.Methods Prospective observational study was performed on88 healthy term newborns. Cord blood was collected for thetotal bilirubin, conjugated bilirubin, unconjugated bilirubinlevel measurement and blood group test. Measurements of totalbilirubin, conjugated bilirubin, and unconjugated bilirubin wererepeated on the 5th day with serum sampling, or as soon as thenewborn appeared to be jaundice.Results Subjects were categorized into hyperbilirubinemia andnon-hyperbilirubinemia newborns. There was a correlationbetween cord blood and the 5th day bilirubin level. By ROCanalysis, cord blood bilirubin level of 2:2.54 md/dL was determined to have high sensitivity (90.5%), specificity of 85%, and accuracy of 86.4%.Conclusions There is a correlation between cord blood bilirubinlevel and hyperbilirubinemia in healthy term newborns. Cordblood bilirubin level at or greater than 2.54 mg/dL can predictthe development of hyperbilirubinemia.